The response of CO₂ emissions to macroeconomic shocks: A panel VAR analysis - Nadeen Omar; Jens Klose (Philipps-University Marburg, School of Business and Economics, 2024)
Global efforts towards mitigating climate change gain momentum; reducing carbon dioxide (CO2) emissions and aiming for zero emissions, or carbon neutrality, is the main goal. Economic factors are main determinants of CO2 emissions coming from production and energy consumption. This paper aims to empirically estimate these economic effects. For this purpose, we employ an unbalanced panel of 78 countries using annual data between 1990 to 2022. We estimate a panel vector autoregression (VAR) model to show the dynamic response of CO2 emissions to a large number of macroeconomic variables. These are: Population, GDP, investment, trade, oil price, renewable energy consumption, inflation, effective exchange rate, and nominal interest rate. Moreover, we perform extensive robustness checks to account for panel heterogeneity by splitting the sample based on: Geographical location, income level, population, and emission level. We find significant responses of CO2 emissions to shocks from population growth, GDP growth, renewable energy consumption, and interest rates.
Keywords: Q54; F64; 330; CO2 emissions; climate change; energy consumption; economic growth; panel VAR